1997
DOI: 10.1152/ajpregu.1997.272.1.r201
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fetal placental embolization and hypoxemia cause hypertension and myocardial hypertrophy in fetal sheep

Abstract: To examine the cardiovascular effects on the fetus of an elevated umbilical vascular resistance resulting in fetal hypoxemia, we embolized the fetal side of the placenta in pregnant sheep and measured cardiovascular and hormonal changes and cellular growth in fetal heart. Chronically catheterized fetal sheep were embolized (n = 6) for 21 days between 0.74 and 0.88 of gestation into the descending aorta until arterial oxygen content was decreased by 40-50% of the preembolization value. Control animals (n = 6) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 0 publications
9
99
2
Order By: Relevance
“…The mechanism by which this occurs is unknown. Elevated blood pressure can cause cardiac hypertrophy possibly by increasing afterload to the heart (Murotsuki et al 1997).…”
Section: Fetal Growthmentioning
confidence: 99%
“…The mechanism by which this occurs is unknown. Elevated blood pressure can cause cardiac hypertrophy possibly by increasing afterload to the heart (Murotsuki et al 1997).…”
Section: Fetal Growthmentioning
confidence: 99%
“…Intrauterine growth retardation is associated with increased neonatal mortality, perinatal complications and long-term neurologic sequelae in preterm infants (1), as well as compromised cardiovascular adaptive capacity already in utero (2)(3)(4). However, few data have been reported regarding early circulatory adaptation after intrauterine growth retardation.…”
mentioning
confidence: 99%
“…Animal studies have demonstrated that placental insufficiency-induced IUGR leads to decreases in oxygenation and substrate availability for the fetus [41][42][43]. Therefore, the uterine ligation or uterine ablation serves as an excellent model for examining idiopathic IUGR and the short-and long-term effects on liver function.…”
Section: Uterine Ligation or Ablation Model Of Undernutrition And Lonmentioning
confidence: 99%